Anti-skid rubber mats flooring effects on the behavioural activity, stress, and milk yield of dairy cows - T., Madihah; W. M., Shaik Mossadeq; S. Z., Ramanoon; T., Rinalfi; R. R., Ayumi; N., Hisamuddin; N., Kamarudin (Department of Veterinary Services Malaysia, 2022)
Data regarding the effects of anti-skid rubber mat-enriched flooring (RM) on dairy cattle production in Malaysia is limited. Hence, this study evaluates the behavioural activity,and milk yield of 40 dairy cows from 2 concrete-floor (CF) (n=10) and 2 anti-skid rubber mat-enriched floor (RM) (n=10) free-stall design farms with intensive management. Cows housed on RM farms showed a significantly (p < 0.05) higher frequency and duration (seconds) of lying down behaviour compared to cows housed on CF, (RM: 4.96 ± 1.33 and 3950.75 ± 744.48 vs. CF: 2.26 ± 1.29 and 1959.6 ± 762.84; mean ± SD). Also, cows housed on RM demonstrated a significantly higher average milk yield (litre/cow/day) than cows housed on CF (p < 0.05). A glucose tolerance test (GTT), adrenocorticotropic hormone (ACTH) challenge, and leukocyte count were conducted (n = 5/farm), to further explore the animals’ energy metabolism and level of stress, respectively. No significant (p > 0.05) differences in the GTT, ACTH, or leukocyte count were observed between cows in CF and RM farms. Thus, the use of RM in dairy farms may improve the milk yield of dairy cattle by promoting the expression of natural activities such as lying down which is important for rumination, without effecting the stress levels or glucose metabolism.